Tax Inclusion as an Effort to Increase Tax Awareness in Learning Islamic Religious Education Courses at Universitas Bina Bangsa - Miftahudin Miftahudin; Saepudin Saepudin (Universitas Muhammadiyah Enrekang, 2023)
This study aims to investigate tax inclusion in courses and analyze their effectiveness and impact on students. Taxes are an important aspect of a country's economy, and a good understanding of taxes is required by citizens, including students as future generations. This research will use qualitative and quantitative approaches by collecting data from students taking tax inclusion courses. Research methods include surveys, interviews, and analysis of exam results as well as assignments related to tax materials. The data will be analyzed using statistical techniques and a descriptive approach. First, this study will evaluate the effectiveness of the tax inclusion learning approach applied in the course. Effectiveness is measured based on students' understanding of tax concepts and their ability to apply that knowledge in real-life situations. Second, this study will identify the impact of tax inclusion in the course on students' social and economic perspectives. Social impacts can include their level of awareness and readiness to pay taxes as responsible citizens. The economic impact can be seen through increased understanding of personal financial management and its effect on investment and consumption. The results of this research are expected to contribute to the development of a higher education curriculum that is more relevant to the needs of the community. In addition, this research can provide input for educational institutions to improve learning approaches that are more effective and interesting in teaching tax materials.